Spiral artery blood volume in normal pregnancies and those compromised by pre-eclampsia. - Moore, R; Ong, S; Tyler, D; Duckett, R; Baker, P; Dunn, W; Johnson, I; Gowland, P (2008)
The aim of this work was to use intravoxel incoherent motion (IVIM) to provide a non-invasive in vivo assessment of the function of the maternal spiral arteries that feed the placenta in normal pregnancy and in pre-eclampsia. Eleven normal pregnant women were scanned at 16, 22, 29 and 35 weeks gestation in a longitudinal study. Nine normal pregnant women and six women with pre-eclampsia were scanned in a cross-sectional study, within 10 days of delivery. The MRI IVIM technique was used to measure the moving blood fraction (f%) at the basal plate. There was no evidence that f% changed with gestational age (P = 0.84), but considering the cross-sectional groups, f% in women with pre-eclampsia was reduced compared with normal pregnancy (mean +/- SD: 36 +/- 5% and 27 +/- 5%; P < 0.005). In conclusion, pregnancies complicated by pre-eclampsia exhibit a reduced fraction of moving blood within the region of the spiral arteries. IVIM performed in the mid-trimester may provide an early means of predicting those pregnancies with an increased likelihood of being complicated by pre-eclampsia.